Social Media Optimization Strategy for Local Fashion Brand Development - Tuti Widiastuti; Adrian Arditiar; Akbar Fauzan Rambe; Eartha Annafi Rasjiddin (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
The development of communication, technology, and the economy in Indonesia encourages the development of promotional activities itself, the birth of various platforms to carry out promotional activities makes competition in business more stringent. Manufacturers are trying to attract the hearts of consumers. Based on this phenomenon, marketing media is needed to be able to reach a wider target market. One of the marketing media that is currently being used is through social media. The purpose of this study is to measure the effect of Instagram ads and celebrity endorsements have on buying interest in local brands. The research uses a quantitative approach with a survey method. Data was collected by distributing questionnaires to respondents.Keywords: Social media optimization, instagram ads, celebrity endorsements, buying interest, local fashion brands ABSTRAKPerkembangan komunikasi, teknologi, dan ekonomi di Indonesia mendorong perkembangan kegiatan promosi itu sendiri, lahirnya berbagai platform untuk menjalankan kegiatan promosi membuat persaingan dalam berbisnis menjadi lebih ketat. Para produsen berusaha untuk menarik hati konsumennya. Berdasarkan fenomena tersebut, diperlukan media untuk menjangkau target pasar yang lebih luas. Salah satu media pemasaran yang saat ini digunakan adalah melalui media sosial. Tujuan dari penelitian ini adalah untuk mengukur pengaruh instagram ads dan endorsement selebgram. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Pengumpulan data dilakukan dengan menyebarkan kuesioner kepada responden.Kata Kunci: Optimasi media sosial, instagram ads, endorsment selebgram, minat beli, brand fashion lokal.